MAIN PROBLEMS SMALL BUSINESSES FACED IN THE SERVICE SECTOR - Sultonov, Shodiyor Аbdukhаlilovich (THE INNOVATION ECONOMY, 2026)
This article analyzes the main problems faced by small business entities in the process of operating in the service sector and their impact on economic development. The service sector is an important component of the modern economy, and small business entities are the main participants in this sector. During the research, institutional, financial, and infrastructural factors hindering the development of small businesses in the service sector were analyzed.